Transcranial Doppler Study Among Children with Sickle Cell Anaemia Vs Normal Children - Lakhkar, BB; Lakhkar, BN; Vaswani, P (Journal of Nepal Paediatric Society, 2012)
Introduction: Role of transcranial Doppler in prevention of stroke in sickle cell children has been well appreciated. Studies are being done to develop the protocol in children. Since we don’t find stroke very commonly in this part of the world, this study was done in order to see the prevalence of abnormal flow velocity in sickle children attending sickle cell clinic. The aims of this study were to measure mean flow velocity in different vessels in homozygous sickle cell patients using transcranial Doppler study, to compare the mean velocity in sickle children with age and sex matched controls and to correlate mean velocity with headache or stroke if any and also to correlate mean velocity with number of transfusions. Materials and Methods: The study was done in Paediatric wards. It was a prospective crosssectional comparative study. Twenty six children below 14yrs of age with homozygous sickle cell disease attending the Sickle cell clinic were selected as the cases. Forty cases of similar age and sex were recruited as normal control group. Transcranial Doppler was done in six different vessels in both the groups and mean flow velocity was measured. Mean flow velocity was correlated with symptoms and number of transfusions. Velocity was classified as normal (<170cm/sec), conditional (170-199cm/sec) or abnormal (>200cm/sec). Statistical analysis was done using SPSS 10 software. Results: In normal age and sex matched controls mean blood flow velocity was 50cm/sec where as in the cases of sickle cell disease was 180cm/sec. Maximum mean velocity was observed in middle and posterior cerebral artery. In two Sickle cell cases (8%) blood flow velocity was abnormal, these children had headache though received 5-10 transfusions/year. In only 4% sickle cell children flow velocity was normal and rest had conditional velocity. Among these children 39% received less than 5 and rest received 5-9 transfusions /yr and had no symptoms of stroke. Conclusions: Flow velocity measured by Transcranial Doppler is highest in middle cerebral artery and Posterior cerebral artery which appear to be the best arteries for this test in this region. Flow velocity was significantly high in children with sickle cell disease as compared to normal children. Prevalence of abnormal flow velocity in our children was 8% and children with abnormal mean flow velocity presented with headache. J. Nepal Paediatr. Soc. 32(2) 2012 146-149 doi: http://dx.doi.org/10.3126/jnps.v32i2.5681